ANALISIS KINERJA SATUAN POLISI PAMONG PRAJA KABUPATEN BLORA DALAM PENANGANAN PEDAGANG KAKI LIMA - Utomo, Yahya Rikaro; Widowati, Nina (Journal of Public Policy and Management Review, 2017)
Police Civil Service Unit (Satpol PP) is the fundamental duty of local governments to enforce local laws, organizing public order and public tranquility. If it is associated with municipal police Organizational Performance Blora, performance assessment carried out in connection with the work being done, namely to enforce the regulations in dealing with street vendors (PKL). The purpose of this study is to describe how the performance of municipal police Blora. Researchers used five dimensions of performance by Dwiyanto to determine the performance of Police Civil Service Unit (Satpol PP) Blora region. The method used was a case study with a qualitative approach. Data collection techniques used were interviews, observation, and study documentation. The results of the field show for Productivity, minimal number of personnel and the budget led to productivity is not going well. Dimensions of service quality is quite good which the services rendered in the form of policing has been implemented as planned, as well as coordination with relevant parties has been running well. Aspiration street vendors to get the relocation has not been able to be realized by the municipal police in cooperation with the relevant parties is also the basis why responsivity be no good. Responsibility pretty good views of the enforcement of regulations in the application of the sanction. Management of websites are still not optimal create municipal police accountability to the community becomes less good, and less increase the interest of public participation in monitoring their performance. Based on the research that has been done, the researchers concluded that the performance of Police Civil Service Unit (Satpol PP) is felt not maximized in dealing with street vendors because of five dimensions used as a benchmark still more numerous dimensions that has not gone well.